Manual of Exercise Testing 2007
DOI: 10.1016/b978-0-323-03302-2.50007-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Electrocardiogram

Abstract: MANUAL OF EXERCISE TESTING1975-Simoons and Hugenholtz 5 reported Frank lead vectorcardiographic changes during exercise in normal subjects. The direction and magnitudes of time-normalized P, QRS, and ST vectors and other QRS parameters were analyzed during and after exercise in 56 apparently healthy men, ages 23 to 62 years. The PR interval and the P-wave amplitude increased during exercise. Direction of the P vectors did not change, differing with previous reports that had noted changes consistent with right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 132 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Similar reductions in diagnostic accuracy are found when the effects of digoxin, LV hypertrophy, and resting ST depression are removed from the analysis. 83 Many other studies have confirmed these findings and echo these limitations. Combined with estimates of exercise capacity, the standard exercise ECG has been shown to be prognostic of future cardiac events.…”
Section: Examination Techniques For the Diagnosis Of Cadmentioning
confidence: 86%
“…Similar reductions in diagnostic accuracy are found when the effects of digoxin, LV hypertrophy, and resting ST depression are removed from the analysis. 83 Many other studies have confirmed these findings and echo these limitations. Combined with estimates of exercise capacity, the standard exercise ECG has been shown to be prognostic of future cardiac events.…”
Section: Examination Techniques For the Diagnosis Of Cadmentioning
confidence: 86%